Peran Modal Sosial Pada Kelompok Tani Tekad Bersama Di Desa Minanga Kecamatan Pusomaen Kabupaten Minahasa Tenggara - Nabu, Anisa; Jocom, Sherly Gladys; Sendow, Martha Marejke (AGRI-SOSIOEKONOMI, 2024)
The purpose of this study was to analyze the role of social capital in the Tekad Bersama Farmer Group in Minanga Village, Posumaen District, Southeast Minahasa Regency. The research lasted for 2 months, from November to December 2022, conducted in Minanga Village, Posumaen Sub-district, Southeast Minahasa Regency. The data used in this research is primary data conducted by direct interviews to rice paddy farmers, while secondary data is obtained from the internet, books, journals and from the Minanga Village Office and reports that have a close relationship with the research. The sampling method in this study uses a purposive sampling method to one Tekat Bersama Farmer Group that has cultivated rice paddy plants, with a total of 16 respondents who cultivate rice paddy plants, landowners who are around the research location. The analysis used in this research is the Likert scaling analysis method, analyzing the role of social capital in farmer groups. The results showed that the role of social capital in the Tekad Bersama Farmer Group in Minanga Village in the role of trust got a score of 351 with a percentage value of 87.75%, in the role of the network got a score of 350 with a percentage value of 87.5%, and in the role of norms got a score of 333 with a percentage value of 83.25%, so that the overall score obtained from 16 respondents of farmer group members was 1,034 with a percentage of 86.16% which was classified as very instrumental.